2016
DOI: 10.11152/mu.2013.2066.181.sff
|View full text |Cite
|
Sign up to set email alerts
|

Is the spleen stiffness value acquired, using acoustic radiation force impulse (ARFI) technology, predictive of the presence of esophageal varices in patients with cirrhosis of various etiologies?

Abstract: Aim: This study's aim was to determine the accuracy of the spleen stiffness value acquired using acoustic radiation force impulse (ARFI) technology, to predict the presence of esophageal varices (EVs) in patients with liver cirrhosis of various etiologies. Material and methods: Of the 366 enrolled patients, 192 had hepatitis B virus, 74 had hepatitis C virus, and 100 had alcohol-related cirrhosis. All patients underwent biochemical tests, gastrointestinal endoscopy, and liver and spleen elas-tography by ARFI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Moreover, some studies have shown that spleen stiffness value acquired using ARFI may predict the presence of oesophageal varices in cirrhotic patients. In particular, Park et al[32] demonstrated that the AST to ALT ratio score, APRI score, PLT, PLT/spleen diameter ratio and spleen elastography variables were all independently associated with oesophageal varices. However, the multivariate analysis revealed that only spleen elastography was associated with oesophageal varices.…”
Section: Emerging Non-invasive Assessment Of Extensive Fibrosis or CImentioning
confidence: 99%
“…Moreover, some studies have shown that spleen stiffness value acquired using ARFI may predict the presence of oesophageal varices in cirrhotic patients. In particular, Park et al[32] demonstrated that the AST to ALT ratio score, APRI score, PLT, PLT/spleen diameter ratio and spleen elastography variables were all independently associated with oesophageal varices. However, the multivariate analysis revealed that only spleen elastography was associated with oesophageal varices.…”
Section: Emerging Non-invasive Assessment Of Extensive Fibrosis or CImentioning
confidence: 99%
“…However, Park et al demonstrates that the usefulness of spleen elastography in detecting esophageal varices depends on the cause of cirrhosis. According to this study spleen elastography is not a reliable predictor of esophageal varices induced by alcoholic cirrhosis ( 33 ) . According to available studies, spleen elastography is not useful in assessing the grade of esophageal varices ( 27 , 33 35 ) .…”
Section: Correlation Between Portal Hypertension Esophageal Varices mentioning
confidence: 79%
“…According to this study spleen elastography is not a reliable predictor of esophageal varices induced by alcoholic cirrhosis ( 33 ) . According to available studies, spleen elastography is not useful in assessing the grade of esophageal varices ( 27 , 33 35 ) . Single studies show that spleen stiffness correlates with clinical history of variceal bleeding ( 36 37 ) , but its utility in determining the risk of bleeding from esophageal varices requires further investigation.…”
Section: Correlation Between Portal Hypertension Esophageal Varices mentioning
confidence: 79%